2022
DOI: 10.36306/konjes.1116729
|View full text |Cite
|
Sign up to set email alerts
|

Çift Yüzlü Fotovoltaik Panellerin Farklı Zemin Koşullarında Performansının İncelenmesi

Abstract: Photovoltaic (PV) panels are generally used for monofacial applications due to the back surface coating materials. When the coating material is transparent, it is defined as bi-facial PV. In this study, the variable albedo effects on bi-facial PVs in different ground conditions were examined. The results were compared with monofacial PV panels in the same conditions for the Konya region. Bifacial PV panels were analyzed under white, sand, and asphalt ground conditions. Simulations were made by the PVsyst progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…These tools include sizing PV systems, calculating energy yield, and estimating the financial return on investment. In the literature, studies from Turkey [27][28][29][30][31][32] and around the world [33][34][35][36][37] analyzed PV systems using PVsyst. For example, Aksoy et al [38] performed performance analysis of three different cells, monocrystalline, polycrystalline, and amorphous silicon, with a fixed installed power of 300 kWp using PVsyst in Konya, Turkey.…”
Section: Methodsmentioning
confidence: 99%
“…These tools include sizing PV systems, calculating energy yield, and estimating the financial return on investment. In the literature, studies from Turkey [27][28][29][30][31][32] and around the world [33][34][35][36][37] analyzed PV systems using PVsyst. For example, Aksoy et al [38] performed performance analysis of three different cells, monocrystalline, polycrystalline, and amorphous silicon, with a fixed installed power of 300 kWp using PVsyst in Konya, Turkey.…”
Section: Methodsmentioning
confidence: 99%
“…Some simulations can be found in the literature using PVsyst. For example, Aksoy et al [25] modeled a bifacial PV system using PVsyst with various grounds, including white, sand, and asphalt in Konya. They found that bifacial systems in asphalt, white, and sand grounds can produce 3.5%, 15.9%, and 7.2% more electricity, respectively, compared to monofacial systems.…”
Section: Yearsmentioning
confidence: 99%
“…Obtained results were compared with monofacial systems. The highest electricity generation was obtained from bifacial PV systems with white ground [26]. In another study for Turkey, modeling was made using PVsyst for the roofs of houses in various directions.…”
Section: Introductionmentioning
confidence: 99%